The Imagined Infant: An Introduction to the Section. Issue 1 (1st January 2020) - Mayes, Linda
ABSTRACT: The papers in this special issue were delivered at the inaugural Anne Marie Sandler Symposium in Infant Mental Health. The theme of the imagined baby, around which each of these papers is oriented, is central to Anne Marie Sandler's early work with congenitally blind infants. Indeed, the notion of the imagined baby is a key psychoanalytic developmental idea for the parent-infant relationship and the infant's emerging self. Each of these papers focuses on how clinicians may observe and understand the imagined infant and use that idea to understand the parent-infant relationship.